THE USE OF COMMUNITY LANGUAGE LEARNING METHOD TO IMPROVE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMP MUHAMMADIYAH 2 PEKANBARU - Nur Kemala Sari Kemala Sari; Jismulatif '; M. Syarfi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research was to find out if the community language learning method could improve students’ speaking ability of the second year students of SMP Muhammadiyah 2 Pekanbaru.The participants were 30 students. The data was collected by using observation sheets, speaking tests, and field notes. The test was used to collect the quantitative data and the observation sheets were used to collect the qualitative data. After accomplishing this research, the writer concludes that the use of CLL method in speaking recount text can improve the students’ speaking ability. The result of pre-test shows the average score of students speaking ability was 45.5. It improved to 67,7 on the post-test 1 and 76,7 on the post-test 2. It was also proved that that the use Community Language Learning could improve the students’ behavior in learning especially in speaking ability. They are more active and have a great motivation during the process of teaching and learning since they are free to explore their idea and share to their friends. In addition, applying story telling technique could also improve students’ ability to speak English in terms of grammar, vocabulary, pronunciation, fluency, and comprehension. Keywords: Community Language Learning method, Speaking Ability